Associations of metabolic factors and adipokines with pain in incipient upper extremity soft tissue disorders: a cross-sectional study. Issue 8 (19th August 2013) - Rechardt, Martti; Shiri, Rahman; Lindholm, Harri; Karppinen, Jaro; Viikari-Juntura, Eira
Abstract : Objectives: Earlier studies have suggested associations between metabolic factors and musculoskeletal pain or disorders. We studied the associations of obesity, lipids, other features of the metabolic syndrome and adipokines (adiponectin, leptin, resistin, visfatin) with upper extremity pain in a clinical population with incipient upper extremity soft tissue disorders (UESTDs). Design: A cross-sectional study. Setting: Primary healthcare (occupational health service) with further examinations at a research institute. Participants: Patients (N=163, 86% were women) seeking medical advice in the occupational health service due to incipient upper extremity symptoms with symptom duration of <1 month were referred for consultation to the Finnish Institute of Occupational Health from Spring 2006 to Fall 2008. We included all actively working subjects meeting diagnostic criteria based on physical examination. We excluded subjects meeting predetermined conditions. Outcome measure: Pain intensity was assessed with visual analogue scale and dichotomised at the highest tertile (cut-point 60). Results: Obesity (adjusted OR for high waist circumference 2.9, 95% CI 1.1 to 7.3), high-density lipoprotein cholesterol (OR 3.9, 95% CI 1.4 to 10.1 for low level) and triglycerides (OR 2.6, 95% CI 1.0 to 6.8 for high level) were associated with pain intensity. Of four adipokines studied, only visfatin was associated with upper extremity pain (adjusted OR 1.4, 95% CI 1.0 to 2.1 for 1SD increase in level). Conclusions: Abdominal obesity and lipids may have an impact on pain intensity in UESTDs. They may intensify pain through proinflammatory pain-modifying molecular pathways or by causing soft tissue pathology and dysfunction of their supplying arteries. Of four adipokines studied only one (visfatin) was associated with pain intensity. In the future, further studies are required to better understand the relationship between metabolic factors and UESTDs.